Variation of Chironomidae (Insecta: Diptera) trophic guilds and their relation with trophic state in reservoirs in the semiarid - Pereira, Valéria dos Santos; Azevêdo, Daniele Jovem; Azevêdo, Evaldo de Lira; Molozzi, Joseline (Ciência e Natura, 2022)
The Chironomidae larvae are sensitive to variations in aquatic ecosystem conditions. We aim to analyze the variation of Chironomidae trophic guilds and their relation to the trophic state index in reservoirs in the semiarid. The study was conducted from 66 sites, distributed in the littoral zone of three reservoirs of Piranhas-Assu river, during June and December of 2014. The larvae were collected, and after identification, were classified in functional trophic groups. We applied the Trophic Status Index of Carlson, modified by Toledo for trophic classification. Sabugí reservoir was the only classified as mesotrophic (52,60±3,64) in June, where the greatest levels of diversity also occurred in the trophic guilds: gatherer-gollector (9 genera), predator (6 genera) and filterer-collector (1 genus). Higher levels of eutrophication occurred in Passagem das Traíras reservoir (84,99±6,19), the same with the smallest diversity in the guilds: gatherer-collector (3 genera) and 1 genus in the other categories. The variation of trophic guilds has been associated with trophy levels, because higher levels of degradation eliminate sensitive species, reducing the number of taxa. Thus, the Chironomidae trophic guilds demonstrate potential capacity for indicating the degree of impact to which the reservoirs are submitted.